The Omnibus Method In Indonesia’s Legislation Formation System - Usihen, Min; Anshari, Tunggul; Riyanto, R. Benny; Widiarto, Aan Eko (CV. AFDIFAL MAJU BERKAH, 2025)
This study seeks to analyze and evaluate the implementation of the omnibus method within Indonesia's legislative framework. The primary focus of the research is to examine how this method streamlines the regulatory structure by merging multiple laws into a single, unified regulation. A qualitative methodology is employed, involving the analysis of relevant legal documents, existing laws, regulations, and academic literature. The sample population includes various Indonesian laws and regulations impacted by the omnibus method. The findings indicate that while the omnibus method significantly reduces legal complexity, it also introduces concerns regarding potential overlaps and conflicts within the legal system.